Annual Versus Biannual Mass Azithromycin Distribution and Malaria Parasitemia During the Peak Transmission Season Among Children in Niger. Issue 6 (June 2018) - Oldenburg, Catherine E.; Amza, Abdou; Kadri, Boubacar; Nassirou, Beido; Cotter, Sun Y.; Stoller, Nicole E.; West, Sheila K.; Bailey, Robin L.; Porco, Travis C.; Keenan, Jeremy D.; Lietman, Thomas M.; Gaynor, Bruce D.
Abstract : Background: Azithromycin has modest efficacy against malaria, and previous cluster randomized trials have suggested that mass azithromycin distribution for trachoma control may play a role in malaria control. We evaluated the effect of annual versus biannual mass azithromycin distribution over a 3-year period on malaria prevalence during the peak transmission season in a region with seasonal malaria transmission in Niger. Methods: Twenty-four communities in Matameye, Niger, were randomized to annual mass azithromycin distribution (3 distributions to the entire community during the peak transmission season) or biannual-targeted azithromycin distribution (6 distributions to children <12 years of age, including 3 in the peak transmission season and 3 in the low transmission season). Malaria indices were evaluated at 36 months during the high transmission season. Results: Parasitemia prevalence was 42.6% (95% confidence interval: 31.7%–53.6%) in the biannual distribution arm compared with 50.6% (95% confidence interval: 40.3%–60.8%) in the annual distribution arm ( P = 0.29). There was no difference in parasite density or hemoglobin concentration in the 2 treatment arms. Conclusions: Additional rounds of mass azithromycin distribution during low transmission may not have a significant impact on malaria parasitemia measured during the peak transmission season.